2003
DOI: 10.1159/000075308
|View full text |Cite
|
Sign up to set email alerts
|

Rising Incidence of Reflux Oesophagitis in Patients Undergoing Upper Gastrointestinal Endoscopy

Abstract: Background: In the literature a lot of epidemiological data is present but little is known on the yearly incidence of oesophagitis and Barrett’s oesophagus. For this reason a cross-sectional study was done to explore the yearly incidence of these conditions in patients sent for upper gastrointestinal endoscopy. Methods: All patients diagnosed with reflux oesophagitis, Barrett’s oesophagus or hiatus hernia in a 10-year period were included. Results: In the period of 10 years 11,691 consecutive patients underwen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
0
5

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 4 publications
(5 reference statements)
4
11
0
5
Order By: Relevance
“…However, it is not the exam of choice for diagnosing laryngopharyngeal reflux. Our results are similar to findings of some other authors (14,16) . Esophageal motor activity revealed that LES average pressure did not differ between patients with dysphonia and controls.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, it is not the exam of choice for diagnosing laryngopharyngeal reflux. Our results are similar to findings of some other authors (14,16) . Esophageal motor activity revealed that LES average pressure did not differ between patients with dysphonia and controls.…”
Section: Discussionsupporting
confidence: 93%
“…Hiatal hernia, an important GERD pathogenic factor, was diagnosed in 65% of G1 patients and in 60% of G2 (P = 0.77), as also observed by Loffeld and Putten (16) . According to Koufman et al (13) , endoscopy is an excellent method to evaluate the esophagus.…”
Section: Discussionsupporting
confidence: 76%
“…A idade média dos pacientes com DRGE (36,8 ± 11,2) foi semelhante à referida por SOMANI et al (36) , porém inferior à publicada por outros autores (3,25,27,32) . O diagnóstico de HHD foi realizado em 76% do pacientes do grupo 1, resultado semelhante ao observado por LOFFELD e PUTTEN (26) . A HHD tem sido considerada como importante fator patogênico da DRGE.…”
Section: Discussionunclassified
“…Em estudo epidemiológico realizado na Holanda, LOFFELD e PUTTEN (26) observaram que nos últimos 10 anos houve aumento do número de pacientes com esofagite de refluxo gastroesofágico em graus 1 e 2. Coincidentemente, foi observado nesta série que dos 20 pacientes com esofagite erosiva, 15 apresentaramna em graus leve e moderado (1 e 2).…”
Section: Discussionunclassified
See 1 more Smart Citation